PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) TERHADAP HASIL BELAJAR MAHASISWA - Roby Agun Guntara (Sekolah Tinggi Pariwisata Mataram, 2021)
The purpose of this study was to determine the effect of the Think-Pair-Share cooperative learning model on the learning outcomes of sports coaching education students. The method used was the quantitative method with the type of experimental research. The sample consisted of 20 people from 40 people. The number of students from the Sports Coaching Education Study Program were randomly selected. Data collection was carried out by using written tests and research questionnaires. Data analysis used descriptive statistics and t-test. The results obtained from this study that there is a significant influence of the Learning Model on learning outcomes, this is evidenced by sig 0.006 <0.05F count 8,066. So, it can be said that the use of TPS-type Cooperative Learning Model can contribute to achieving student learning outcomes for the better.